ILCA: Research and information for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The International Livestock Centre for Africa (ILCA) is one of 13 centres supported by the Consultative Group on International Agricultural Research (CGIAR). It is one of two centres dedicated to livestock research; the other is the International...